Can media and text analytics provide insights into labour market conditions in China? - Jeannine Bailliu; Xinfen Han; Mark Kruger; Yu-Hsien Liu; Sri Thanabalasingam (Bank of Finland, Institute for Economies in Transition (BOFIT), 2018)
The official Chinese labour market indicators have been seen as problematic, given their small cyclical movement and their only-partial capture of the labour force. In our paper, we build a monthly Chinese labour market conditions index (LMCI) using text analytics applied to mainland Chinese-language newspapers over the period from 2003 to 2017. We use a supervised machine learning approach by training a support vector machine classification model. The information content and the forecast ability of our LMCI are tested against official labour market activity measures in wage and credit growth estimations. Surprisingly, one of our findings is that the much-maligned official labour market indicators do contain information. However, their information content is not robust and, in many cases, our LMCI can provide forecasts that are significantly superior. Moreover, regional disaggregation of the LMCI illustrates that labour conditions in the export-oriented coastal region are sensitive to export growth, while those in inland regions are not. This suggests that text analytics can, indeed, be used to extract useful labour market information from Chinese newspaper articles.
URN:NBN:fi:bof-201804231455
Keywords: C38; C55; E24; E27; 330